PENDEKATAN PREVENTIF PENYALAHGUNAAN NARKOBA PADA SISWA SEKOLAH MENENGAH KEJURUAN - Dian Wuri Astuti; Anwarudin; Andri Suryanto; Ayudyah Esta Halifah; Nedike Putri Hary; Yosefina Ina Kii; Hikmah Nabila Djanna; Silvana Maria Dima; Sadfa Dinda Maharani Wokanubun (Media Literasi Indonesia, 2026)
Drug abuse among adolescents, particularly students of Vocational High Schools (SMK), has become a serious problem that affects health, academic achievement, and the future of the younger generation. This community service activity aims to increase the knowledge and awareness of SMK students regarding the dangers of drug abuse through a preventive approach in the form of health education and drug screening examinations. The methods employed include interactive counseling, discussions, and amphetamine drug screening. The results indicate an improvement in students’ understanding of the types, impacts, and legal consequences of drug abuse, as well as the development of preventive attitudes in maintaining personal well-being and a drug-free school environment.